2018
DOI: 10.1042/bsr20171716
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer study of the transcriptional regulation of uricogenesis in human tumours: pathological and pharmacological correlates

Abstract: Uric acid (UA) is the end product of the catabolism of purines, and its serum levels are commonly increased in cancer patients. We aimed to explore the transcriptional regulation of tumour uricogenesis in human tumours, and relate uricogenesis with tumour pathological and pharmacological findings. Using data from The Cancer Genome Atlas (TCGA), we analysed the expression levels of xanthine dehydrogenase (XDH) and adenine phosphoribosyltransferase (APRT), two key enzymes in UA production and the purine salvage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Although there was a significant positive correlation between XDH expression and macrophage infiltration in the TIMER database, only a positive trend was found between XDH expression and CD68 + macrophage infiltration in this small group of HCC tissues. Indeed, Saidak et al indicated that XDH expression is linked to an immune infiltrate in tumors [55]. XDH expression initiates several immune-related pathways, including the T cell receptor, PI3K-AKT, and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a significant positive correlation between XDH expression and macrophage infiltration in the TIMER database, only a positive trend was found between XDH expression and CD68 + macrophage infiltration in this small group of HCC tissues. Indeed, Saidak et al indicated that XDH expression is linked to an immune infiltrate in tumors [55]. XDH expression initiates several immune-related pathways, including the T cell receptor, PI3K-AKT, and MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FTCD was found to be associated with the sensitivity of chemotherapeutic drug methotrexate by using a CRISPR-Cas9-based screen [ 32 ]. XDH, a rate-limiting enzyme to catalyze the final steps of purine metabolism, was found significantly decreased and served as a useful predictor of poor prognoses in several cancer types [ 33 ]. Uric acid, which was transformed by XDH, was found to modulate tumor cell sensitivity to the antimetabolite 5-FU, one of the most commonly used anticancer drugs in the clinic [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that XDH expression levels are associated with tumor growth. Elevated expression of XDH is associated with tumor infiltration as well as upregulated proinflammatory and immune-related cytokine expression [31]. XDH also served as a useful biological parameter in a pan-cancer study [31], but its molecular function in neuronal or other cells remains largely unexplored given that it may be either reversibly or irreversibly converted to XO in mammals [32,33].…”
Section: Y P E X D H -1 ( C H R 1 ) X D H -1 ( O K 3 2 3 4 ) X D H -1 ( C H R 1 ) ; E X [ X D H -1 G E N E ] X D H -1 ( O K 3 2 3 4 ) ; Ementioning
confidence: 99%
“…Elevated expression of XDH is associated with tumor infiltration as well as upregulated proinflammatory and immune-related cytokine expression [31]. XDH also served as a useful biological parameter in a pan-cancer study [31], but its molecular function in neuronal or other cells remains largely unexplored given that it may be either reversibly or irreversibly converted to XO in mammals [32,33]. In contrast, since invertebrate XOR is present only as XDH [33], C. elegans is thought to be a useful model for studying XDH.…”
Section: Y P E X D H -1 ( C H R 1 ) X D H -1 ( O K 3 2 3 4 ) X D H -1 ( C H R 1 ) ; E X [ X D H -1 G E N E ] X D H -1 ( O K 3 2 3 4 ) ; Ementioning
confidence: 99%